P2X4R Overexpression Upregulates Interleukin-6 and Exacerbates 6-OHDA-Induced Dopaminergic Degeneration in a Rat Model of PD - Ma, Jiangnan; Gao, Jinzhao; Niu, Mengyue; Zhang, Xiaona; Wang, Jing; Xie, Anmu (Frontiers in Aging Neuroscience, 2020)
The pathogenesis of Parkinson's disease (PD) remains elusive. Current thinking suggests that the activation of microglia and the subsequent release of inflammatory factors, including interleukin-6 (IL-6), are involved in the pathogenesis of PD. P2X4 receptors (P2X4R) are part of P2X superfamily of ion channels activated by ATP. To study the possible effect of the ATP-P2X4R signal axis on IL-6 in PD, lentivirus carrying the P2X4R-overexpression gene or empty vector were injected into the substantia nigra (SN) of rats, followed by treatment of 6-hydroxydopamine (6-OHDA) or saline one week later. The research found the relative expression of P2X4R in the 6-OHDA-induced PD rat model was notably higher than those in the normal. And P2X4R overexpression could upregulate the expression of IL-6, reduce the amount of dopaminergic (DA) neurons in the SN of PD rats, suggesting that P2X4R may mediate the production of IL-6 to damage DA neurons in the SN. Our data revealed the important role of P2X4R in modulating IL-6, which leads to neuroinflammation involved in PD pathogenesis.